Restrictions on free actions of the alternating group A_6 on products of spheres - Plakhta, L. P. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We prove that the alternating group A_6 cannot freely act on (S^n)^5 We give an example of free action of the alternating group A_4 on (S^n)^3.